2005
DOI: 10.1620/tjem.205.45
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Flow-Mediated Dilatation and Exercise Capacity in Highly Trained Endurance Athletes

Abstract: Brachial artery ultrasound during reactive hyperemia is a noninvasive method of assessing peripheral endothelium-dependent vasodilatation. Aerobic exercise has the potential to improve local endothelial function. We sought to analyze the effects of regular aerobic training on brachial artery endothelial function in endurance athletes. We studied diameter and blood flow of the brachial artery in 32 endurance male athletes and 30 healthy male subjects. In the same subjects flow-mediated dilatation of the brachia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
4
27
0
1
Order By: Relevance
“…27 A third possibility is that higher cardiorespiratory fitness may act to maintain endotheliumdependent vasodilation with age, as previously reported. 28 LV structure LV wall thickness increases with age not only in individuals with hypertension but also in normotensive adults. 4 Moreover, physiological hypertrophy ('the athlete's heart'), characterized by an increase in LV chamber size and mass, is observed in adults with a high level of cardiorespiratory fitness.…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…27 A third possibility is that higher cardiorespiratory fitness may act to maintain endotheliumdependent vasodilation with age, as previously reported. 28 LV structure LV wall thickness increases with age not only in individuals with hypertension but also in normotensive adults. 4 Moreover, physiological hypertrophy ('the athlete's heart'), characterized by an increase in LV chamber size and mass, is observed in adults with a high level of cardiorespiratory fitness.…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…These findings are supported by several studies that found that baseline brachial artery diameter was not altered after the consumption of a single HFM 29,65,81,102 or after exercise training 47 .…”
Section: Brachialsupporting
confidence: 78%
“…Our findings are supported by research that has shown that endothelium-dependent vasodilation was not different regardless of training status in healthy, young men 18 . However, the data on the influence of training on FMD is mixed as another cross sectional study has found that young male runners demonstrated significantly greater FMD (≈ 35%) compared to young, sedentary males (17.1 ± 2.3% vs. 11.2 ± 1.7%, runners vs. sedentary, respectively, p = 0.002) 47 .…”
Section: Brachialmentioning
confidence: 99%
See 1 more Smart Citation
“…The athlete's heart has been shown to be associated with rhythm and conduction alterations, QRS voltage changes caused by ventricular hypertrophy, and repolarization abnormalities, as a consequence of morphologic and physiological cardiac adaptation that occurs with regular physical training (Huston et al 1985;Kasikcioglu et al 2005). In contrast, we have recently showed that QT interval duration and dispersion is not different in trained athletes and control subjects (Turkmen et al 2004).…”
mentioning
confidence: 88%